Β-carotene, iron and zinc content, effect of storage and type of cooking in sweet potato (Ipomoea batatas L) genotypes - Carpio R., Rossemary V. (2017)
Sweet potato (Ipomoea batatas L) is the main component in the diet of millions of people living in tropical countries, and an improvement in β-carotene content could increase the supply of vitamin A to meet a greater part of the daily requirements of people. In the present study, the content of β-carotene (BC), iron (Fe) and zinc (Zn) were determined in 25 genotypes of sweet potato from two localities: La Molina and SanRamón. Furthermore, the changes in BC content in seven sweet potato genotypes were investigated using different cooking methods and storage times. The content of BC was measured via absorbance at 450 nm and identified through HPLC while Fe and Zn content were determined through ICP-OES techniques. The results show significant variation between genotype, environment and in the genotype-environment interaction. BC content in freshly harvested raw root ranged from 7.62 to 18.93 mg /100 g in fresh weight (PF), iron content ranged from 0.40 to 0.9 6mg/100 g PF and the zinc content ranged from 0.25 to 0.51 mg/100 mg PF. Genotypes 440442 and 440518 showed the highest levels of BC in bothlocalities. Differences in BC content were found among cooking methods and storage times. BC concentration in boiled roots (15.15 mg/100 g PF) evaluated was higher than in baked roots (14.29 mg/100 g PF); however, without differences between genotypes 440442 and 420081 due to the cooking methods. BC content of root increased with storage time, where genotype 440442 showed the highest levels of BC during storage time, while genotypes 440413 and 440513 did not differ during storage time.